Effectiveness of Pretrial in Testing the Legality of Arrest and Detention - Indraswari, Sri Primawati; Chan, Rachel; Lee, Ava (Rechtsnormen: Journal of Law, 2025)
Background: Pretrial procedures play a vital role in testing the legality of arrest and detention, ensuring that individuals' rights are protected against arbitrary detentions. Legal safeguards such as judicial review of arrests are essential in preventing abuses of power by law enforcement agencies. In many jurisdictions, pretrial hearings serve as a critical mechanism to determine whether there is enough evidence to justify continued detention, thus promoting the rule of law and human rights protection. However, the effectiveness of pretrial procedures in safeguarding individuals from unlawful detention remains a topic of debate. Objective: This study aims to evaluate the effectiveness of pretrial hearings in testing the legality of arrest and detention. The research investigates how these procedures influence the protection of individual rights and the overall functioning of the justice system. Method: A qualitative research design was employed, utilizing case studies, legal analysis, and interviews with legal professionals, detainees, and human rights advocates. Data were collected from multiple jurisdictions to assess the impact of pretrial procedures on the legality of detention. Results: The findings suggest that pretrial hearings are an effective mechanism for testing the legality of arrests and detentions, but their application is inconsistent, with some jurisdictions lacking adequate legal frameworks to ensure timely and fair reviews. Conclusion: The study concludes that while pretrial hearings can significantly contribute to the protection of individual rights, improvements in procedural consistency and access to legal representation are needed to enhance their effectiveness.